2012
DOI: 10.1111/j.1439-0531.2008.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycomolecule Modifications in the Seminiferous Epithelial Cells and in the Acrosome of Post‐testicular Spermatozoa in the Alpaca

Abstract: A lectin histochemical investigation of the seminiferous epithelium and acrosomes of spermatozoa present in the efferent ductules and epididymal regions was carried out in the alpaca. The histochemical characterization was performed using a battery of different lectins: Con-A, UEA-I, LTA, WGA, GSA-IB4, SBA, PNA, ECA, DBA, MAL-II and SNA. Sialidase digestion and deglycosilation pre-treatments were also employed. The cytoplasm of the Sertoli cells contained N-linked oligosaccharides with α-D-Man/α-D-Glc and GlcN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Lectin histochemical techniques have been widely used to study the pattern of the glycoconjugates present in the cells of the seminiferous epithelium in many species of vertebrate, including amphibians (Valbuena et al 2010(Valbuena et al , 2011a, fish (Liguoro et al 2004;Desantis et al 2010), birds (Ballesta et al 1991;Bakst et al 2007;Pel aez and Long 2008), mammals (Arya and Vanha-Perttula 1985;Calvo et al 2000;Pinart et al 2001;Morales et al 2002;Desantis et al 2006;Parillo et al 2012) and humans (Arenas et al 1998). This histochemical technique has recently been used to identify changes in the pattern of glycoconjugates of various cell types in apoptosis (Taatjes et al 2008), in particular lectins with affinity for a-D-mannose and b-D-galactose (Bilyy et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lectin histochemical techniques have been widely used to study the pattern of the glycoconjugates present in the cells of the seminiferous epithelium in many species of vertebrate, including amphibians (Valbuena et al 2010(Valbuena et al , 2011a, fish (Liguoro et al 2004;Desantis et al 2010), birds (Ballesta et al 1991;Bakst et al 2007;Pel aez and Long 2008), mammals (Arya and Vanha-Perttula 1985;Calvo et al 2000;Pinart et al 2001;Morales et al 2002;Desantis et al 2006;Parillo et al 2012) and humans (Arenas et al 1998). This histochemical technique has recently been used to identify changes in the pattern of glycoconjugates of various cell types in apoptosis (Taatjes et al 2008), in particular lectins with affinity for a-D-mannose and b-D-galactose (Bilyy et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies describing male genital tract of alpacas. In particular, Parillo et al (2009aParillo et al ( , 2009bParillo et al ( , 2012 reported a detailed distribution of glycosidic residues of glycoconjugates in the epidydimis, testis and spermatozoa. Wang et al (2011) reported that NGF is espressed in the testis of alpaca .…”
Section: Innervation and Immunohistochemical Characteristics Of Epidimentioning
confidence: 99%
“…espermios y comprobamos que la estructura tubular del huarizo presenta la misma complejidad que la de sus progenitores, en una próxima etapa se podrá estudiar el ciclo de desarrollo del epitelio germinativo de los túbulos seminíferos y hacer una caracterización histoquímica usando una batería de lectinas Con-A, VEA-1,LTA, WGA, GSA-IB4, SBA, PNA, ECA, DBA, MAL-II y SNA, comparándola con el trabajo desarrollado por Parrillo et al (2009) con alpacas. Kadwell et al (2001) mostraron que hay una alta similitud genética entre alpaca y vicuña y entre llama y guanaco estudiando ADN mitocondrial y ADN microsatélite.…”
Section: Valenzuela-estrada M; Rippes F and Nuñez Hunclassified